Estrategias narrativas en las plataformas de streaming en el Perú - Giuliana Cassano; James A. Dettleff; Guillermo Vásquez (Les Cahiers ALHIM)
Global streaming platforms arrived in Peru in the second decade of the 21st century. At first, they were large repositories of global content that allowed local audiences to access titles from around the world. They often brought us closer to little-known audiovisual industries in Peru. The first Peruvian content that entered some of these platforms were cultural documentaries and fiction feature films, inscribing themselves in the dynamics of local-global tension, distinctive of these technologies. Titles produced years before they were bought were added to the catalogs of these platforms.This article aims to think about the narrative and industry strategies that are set into play in the dynamics of the entry of our audiovisual cultural products into global platforms. This is in a context where there are also bets on local and regional platforms of the Peruvian audiovisual industry. This article will start from the perspective of media ecology (Innis in Elizondo, 2014) and media convergence (Jenkins, 2008), understanding that these streaming platforms are integrated into the contemporary television ecosystem and influence the reconfiguration of the television medium as a cultural system.